1989
DOI: 10.3758/bf03198475
|View full text |Cite
|
Sign up to set email alerts
|

The negative generation effect: Delineation of a phenomenon

Abstract: In four experiments employing between-list designs, generation was found to have negative effects on free recall of word pairs and on cued recall of the second word. In addition, generation had negative effects on measures of word-pair integration and on clustering in recall. In contrast, positive effects of generation were found on free recall of second words alone, and on a recognition test for memory of the second word. It was concluded that in between-list designs, generation led to greater individual-item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 26 publications
3
57
1
Order By: Relevance
“…It was predicted that under these conditions, generation facilitation should be reduced, particularly for free recall (Schmidt & Cherry, 1989;Slamecka & Kasaiti, 1987). Precisely this pattern of results was shown in Experiment 2.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…It was predicted that under these conditions, generation facilitation should be reduced, particularly for free recall (Schmidt & Cherry, 1989;Slamecka & Kasaiti, 1987). Precisely this pattern of results was shown in Experiment 2.…”
Section: Resultsmentioning
confidence: 58%
“…Previous experiments have shown that generation effects for free recall are sometimes absent or even negative (Hirshman & Bjork, 1988;Schmidt & Cherry, 1989;Slamecka & Kasaiti, 1987). Many, though not all, ofthese failures to show generation facilitation have manipulated encoding conditions between subjects or have used intentional learning procedures, or both.…”
Section: Summary Ofthe Modelingmentioning
confidence: 99%
“…A more complete explanation of the generation effect must rely on interactions between list structure, types of information encoded, and the nature of the memory test (McDaniel et aI., 1988). In a between-subjects design, generation appears to increase individual-item processing at the expense of whole-list organization (Schmidt & Cherry, 1989). On memory tests in which list organization is important (e.g., free recall), the increased individual-item processing and decreased relational processing may lead to no net effect of generation (Slamecka and Katsaiti, 1987), or to a negative generation effect (Schmidt & Cherry, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In a between-subjects design, generation appears to increase individual-item processing at the expense of whole-list organization (Schmidt & Cherry, 1989). On memory tests in which list organization is important (e.g., free recall), the increased individual-item processing and decreased relational processing may lead to no net effect of generation (Slamecka and Katsaiti, 1987), or to a negative generation effect (Schmidt & Cherry, 1989). In contrast, on recognition (Schmidt & Cherry, 1989;Slamecka and Graf, 1978) or cued recall tests (Hirshman & Bjork, 1988;McDaniel et aI., 1988), list organization is less important, and positive effects of generation are found even in betweenlist designs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar frameworks have been adopted to explain bizarre imagery (McDaniel & Einstein, 1986), the concreteness effect (Marschark & Hunt, 1989), and the generation effect (Schmidt & Cherry, 1989). Furthermore, the hypothesis does not seem at odds with Eysenck's (1979) ideas.…”
Section: Encoding and Retrieval Explanationsmentioning
confidence: 91%